Editorial – International Journal of Sustainable Energy Planning and Management Vol 18 - Østergaard, Poul Alberg (International Journal of Sustainable Energy Planning and Management, 2018)
This editorial introduces the 18th volume of the International Journal of Sustainable Energy Planning and Management, which addresses the energy mix of Indonesia, the water-energy nexus in the Drina River Basin, the effects of economic crises on electric utilities, the potential for biogas production in Ukraine and the organisation and ownership of community energy projects.